Psychological Distress and Perceived Stigmatization Among Undergraduates: Do Resilience and Positive Emotions Count? - Chisom E. Ogbonnaya; Emmanuel E.Uye (CV Putra Publisher, 2026)
Perceived stigmatization has remained a recurring problem affecting different individuals such as the undergraduate population. Studies using different predictors of perceived stigmatization have produced varied results. Therefore, this study examines the moderating effects of resilience and positive emotion on psychological distress and perceived stigmatization among undergraduates in a Nigerian university. A cross–sectional survey was adopted while data were conveniently collected from 461 participants using validated questionnaires. Data collected were analyzed using hierarchical multiple regression analysis to test five hypotheses which were accepted at p =.001 level of significance. The result revealed that psychological distress (β = .67, p = .007) and resilience (β = .15, p = .001) predicted perceived stigmatization among study participants. In addition, the result showed that resilience (β = -.01, p = .018) and positive emotions (β = .01, p =.025) moderated between psychological distress and perceived stigmatization among study participants. However, positive emotion did not predict perceived stigmatization among study participants (β = .02, p =.724). The study concludes that resilience and positive emotion provide buffering effects on perceived stigmatization among undergraduates. The study recommends that parents, university authority and other stakeholders should provide psychological services to reduce psychological distress and perceived stigmatization among undergraduates.